Leptogenesis and neutrino mass with scalar leptoquarks - Kåre Fridell (Journal of High Energy Physics)
Abstract Leptoquarks are known to generate a wide range of potentially observable phenomena, and have been searched for in different experiments. We show that the observed baryon asymmetry and neutrino mass scale can both be simultaneously produced in a model featuring scalar leptoquarks while avoiding existing experimental constraints and potentially leading to future observable signatures.